The Convergence of the Interactionist and Behavioral Approaches to Deviance - Gambrill, Eileen D. (1974)
This paper compares two theoretical perspectives on deviance, the behavioral and interactionist. Although these two perspectives arise from separate disciplines and intellectual traditions, we will argue that their approaches to the study of deviance in general and to mental illness in particular share many basic similarities, as well as some important differences, and that an analysis of each helps us understand the limitations and strengths of the other. The behavioral and interactionist perspectives are chosen for examination for three reasons. First, it is our opinion that these two theoretical approaches represent the most creative recent work by sociologists and psychologists on deviant behavior. Second, there are few attempts in the literature to integrate the perspectives (Ullman and Krasner, 1969; Singelmann, 1972; and Akers, 1973 are recent exceptions), and, in fact, the perspectives are often posed as antagonistic. Third, both perspectives share a rejection of the dominant psychiatric conceptualizations of deviant behavior and place greater emphasis on the social context of deviance. The discussion of these two perspectives will compare them by examining their approaches to one form of deviance, mental illness. Attention will be given to the similarities and dissimilarities of these perspectives in terms of concepts, propositions and methodology, with particular attention to areas of actual or potential crossfertilization. In order to focus the comparison, we will first outline some of the basic assumptions of each perspective and then move to the topic of mental illness by examining their treatment of (1) the definition of mental illness, (2) primary deviation, (3) the responses of others to primary deviation, (4) secondary deviation, and (5) the philosophy and methodology of research